STUDI BIAYA DAN PENDAPATAN PENANGKARAN MONYET EKOR PANJANG (Macaca fascicularis Raffles) DENGAN SISTEM TERBUKA, SEMI TERBUKA DAN TERTUTUP (Expenses and Earnings Study of Breeding of Long Tail Macaque with Open, Semi Open, and Closed Systems) - Sugeng Paryadi; Yanto Santosa; Jojo Ontarjo (Media Konservasi, 2006)
The study was conducted to calculate the earning and expenses of three kinds breeding system of long tail macaque i.e open, semi-open and close breeding system, respectively in PT PRESTASI Farma Nusantara, CV New Inquitex Primates Division and CV Wahana Satwa Loka. Discounted cash now analysis for ten years period were used to determine the earning and expenses, using 18% of interest rate. According to NPV, IRR and BCR values for 1000 macaques in captive showed that the earning and expenses were difference between these breeding system, where closed system was higher than the others. Based on product grade, close system was better (level B) than semi-open (level C) and open system (level D).Keyword : Macaca fascicularis, breeding system, expenses, earnings